Development of methods and means of the analysis of strain-gauge experimental researches - Зінченко, В.П.; Зінченко, Н.П. (Proceedings of National Aviation University (archive), 2005)
The analysis of the existing organization of strain-gauge experimental researches of models of flight vehicles in wind tunnels as object of automation is executed and the new technology is offered, and also requirements to functions of information technology and its structure are generated.